Successful Pregnancy in a Case of Behçet's Disease after Treatment with Prednisolone - Shogo Nishii; Koushi Yamaguchi; Mitsuyoshi Amita; Takakazu Saito; Hidekazu Saito; Akihiko Sekizawa (Hindawi Limited, 2020)
A 34-year-old woman (gravida 1, para 0) visited the Division of Reproductive Medicine/National Center for Child Health and Development due to infertility; she had also been suffering from incompletely treated genital ulcers and stomatitis for 10 years. This case was diagnosed as an incomplete-type Behçet's disease (BD) at the Department of Maternal-Fetal Biology/National Center for Child Health and Development. Since no apparent abnormality was found in the general infertility test, artificial insemination with the husband's semen (AIH) was performed for the patient with unexplained infertility, which failed. However, after treating BD with prednisolone, chronic inflammation (stomatitis and genital ulcer) and immunological abnormalities (Th2 and NK cell activity) improved, and conception was possible by AIH. Thus, prednisolone administration may have induced immune tolerance in the patient with BD, which may have contributed to the success of AIH.